1975
DOI: 10.1002/bjs.1800620306
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative problems and management after hepatic resection for blunt injury to the liver

Abstract: The postoperative problems and management of 8 patients following right hepatic lobectomy for blunt liver injury are discussed. Multiple injury and in particular chest injury are of importance. Respiratory distress may be insidious in onset and must be anticipated. Most patients require at least temporary positive pressure ventilation. Liver regeneration is rapid and histological evidence of regenerative hyperplasia is present within 3 days of injury. Hypoglycaemia of a degree sufficient to threaten life may o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

1975
1975
2012
2012

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…PARTIAL hepatectomy in man is known to result in disordered liver function, indicated by abnormal biochemical tests and impaired synthesis of coagulation factors (Vajrabukka et al, 1975). In patients who undergo partial hepatectomy for major hepatic trauma, prolonged hypotension probably contributes to diminished liver function, and observations which we have made in the dog confirmed that the impairment of hepatic function is increased when partial hepatectomy is preceded by periods of total ischaemia of the liver remnant of up to 1 hour (Mackenzie et al, 1975).…”
supporting
confidence: 50%
“…PARTIAL hepatectomy in man is known to result in disordered liver function, indicated by abnormal biochemical tests and impaired synthesis of coagulation factors (Vajrabukka et al, 1975). In patients who undergo partial hepatectomy for major hepatic trauma, prolonged hypotension probably contributes to diminished liver function, and observations which we have made in the dog confirmed that the impairment of hepatic function is increased when partial hepatectomy is preceded by periods of total ischaemia of the liver remnant of up to 1 hour (Mackenzie et al, 1975).…”
supporting
confidence: 50%
“…It is tempting to speculate that novel finding could be explained by an increased proportion of free thyroid hormones after liver surgery, caused by lower thyroid hormone binding proteins concentrations (hypoproteinemia) [15,16]. Another explanation might be based on an assumption that pancreatic surgery – generally - is a more serious procedure with more serious complications and lower free thyroid hormones levels are known to be a manifestation of particularly deep and serious metabolic disturbances.…”
Section: Discussionmentioning
confidence: 99%
“…However, the role played by bile chemical peritonitis on hepatic energy metabolism and regeneration is not well understood. It is thought that sterile intraperitoneal accu mulations of bile may affect liver regeneration because early regeneration, as measured by DNA synthesis, has been reported to be completed within 1 week following hepatic resection [21],…”
Section: Discussionmentioning
confidence: 99%